In Vitro Study of Leishmanicidal Activity of Biogenic Selenium Nanoparticles against Iranian Isolate of Sensitive and Glucantime-Resistant Leishmania tropica - MAHMOUDVAND, Hossein (Iran J Parasitol, 2014)
BACKGROUND: Sensitive and glucantime (MA) resistance Leishmania tropica are referred to those isolates, which are responsive, or non-responsive to one or two full courses of treatment by MA systematically and/or intra-lesionally, respectively. In this study, we evaluated the antileishmanial activity of biogenic selenium nanoparticles (Se NPs) alone and in combination with MA against sensitive and glucantime-resistant L. tropica on in vitro model. METHODS: The Se NPs were synthesized by employing the Bacillus sp. MSh-1. The antileishmanial effects of Se NPs alone and in combination with MA on promastigote and amastigote stages of sensitive and glucantime-resistant L. tropica strains have been investigated using a colorimetric MTT assay and in a macrophage model. In addition hemolytic activity in type O+ human red blood cells and infectivity rate of the promastigotes before and after treatment with the Se NPs was evaluated. RESULTS: In the promastigote stage, various concentrations of Se NPs significantly inhibited (P<0.05) the growth of promastigotes of both strains in a dose-dependent manner. Similarly, Se NPs especially in combination with MA significantly reduced the mean number of amastigotes of both strains in each macrophage. Se NPs showed no hemolytic effect on human RBCs at low concentrations. Moreover, infection rate of macrophages by promastigotes significantly (P<0.05) was reduced when promastigotes pre-treated with Se NPs. CONCLUSION: The findings of this study suggest a first step in the search of Se NPs as a new antileishmanial agent. Further experiments are needed to investigate antileishmanial effects of biogenic Se NPs on L. tropica using a clinical setting.